UNDERSTANDING THE DETERMINANTS OF ENTREPRENEURIAL INTENTION AMONG STUDENTS: A LITERATURE REVIEW APPROACH - Putra, Agung Satria; Yohana, Corry; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The objective of this study is to investigate the impact of entrepreneurship education and self-efficacy on the level of entrepreneurial engagement among students at vocational high school, employing qualitative methods and a literature review approach. The research synthesizes insights from diverse sources, including articles, existing literature, and relevant empirical studies. The results of the literature review suggest that entrepreneurship education plays a significant role in promoting students' intentions to become entrepreneurs. Exposure to entrepreneurial concepts within the school curriculum enhances students' knowledge and instills an entrepreneurial mindset. Additionally, the literature underscores the significance of self-efficacy in each student, playing a crucial role in their ability to effectively manage and operate business in the future.